2013
DOI: 10.5604/17322693.1059549
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes type 2 and Alzheimer disease – one or two diseases? Mechanisms of association

Abstract: Some epidemiological data and pathophysiological evidence suggest similarities and connection of two amyloidoses: diabetes mellitus type 2, (DM2) (non-insulin dependent diabetes mellitus, NIDDM) and Alzheimer's disease (AD). What they have in common is insulin resistance, neurodegeneration, development and progression of dementia, and the fact that in the course of both diseases fibrillar aggregates of specific proteins are accumulated in affected organs. What is more, experimental evidence also supports the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…IR indirectly enhances the activity of glycogen synthase kinase-3β (GSK-3β) and promotes the AD-like Tau hyperphosphorylation in the hippocampus of the mice and rats in animal models of insulin dysfunction ( 46 ). In addition, IR can regulate the activity of γ-secreting enzyme by GSK-3β ( 47 ), promote the synthesis of Aβ40 and Aβ42, inhibit the activity of insulin degrading enzyme and reduce the degradation of Aβ ( 48 ). Furthermore, insulin plays a pivotal role in regulation of energy metabolism, growth, survival and differentiation of neuronal cells via insulin signaling in the brain ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…IR indirectly enhances the activity of glycogen synthase kinase-3β (GSK-3β) and promotes the AD-like Tau hyperphosphorylation in the hippocampus of the mice and rats in animal models of insulin dysfunction ( 46 ). In addition, IR can regulate the activity of γ-secreting enzyme by GSK-3β ( 47 ), promote the synthesis of Aβ40 and Aβ42, inhibit the activity of insulin degrading enzyme and reduce the degradation of Aβ ( 48 ). Furthermore, insulin plays a pivotal role in regulation of energy metabolism, growth, survival and differentiation of neuronal cells via insulin signaling in the brain ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the Introduction, the two diseases present abnormal blood glucose levels, insulin resistance, inflammation, oxidative stress, and neurodegeneration [42, 43]. Nowadays, three ChE inhibitors can be used to delay the symptomatic decline observed in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of white matter is most evident in the frontal and temporal regions, whereas loss of gray matter is most evident in the medial temporal, anterior cingulate, and medial frontal lobes [29]. Regarding the risk of MCI in T2DM patients, epidemiological studies have revealed hazard ratios (HRs) of 1.5 and 1.2 for amnesic MCI and non-amnesic MCI [13,25,[30][31][32], respectively. In addition, a meta-analysis has indicated a relative risk of conversion of MCI to dementia of 1.7 (1.1-2.4) for individuals with T2DM compared to individuals without diabetes [33].…”
Section: Diabetes Cognitive Dysfunction and Dementiamentioning
confidence: 99%